Natural killer-like function of activated T lymphocytes: differential blocking effects of monoclonal antibodies specific for a 90-kDa clonotypic structure. - Hercend, T; Meuer, S; Brennan, A; Edson, M; Acuto, O; Reinherz, E; Schlossman, S; Ritz, J (1984)
A monoclonal antibody termed anti-NKTb has been generated following immunization of mice with cloned human cells (JT9) displaying natural killer (NK)-like activity. This antibody has the capacity to block cytotoxicity of the immunizing clone against several targets. In the present study, anti-NKTb was compared with a monoclonal antibody termed anti-NKTa that had previously been generated against JT9 cells and that had also been shown to block the NK-like function of these cells. The expression of a NKTb determinant, like that of NKTa, was found to be restricted to two NK active clones derived from the same individual, JT9 and JT10, both of which have the same mature T-cell phenotype (T3+, T8+, T11+). Comodulation, immunoprecipitation, and competitive binding experiments showed that both antibodies are directed to the same 90-kDa heterodimer associated with the T3 structure on the cell surface. However, cytotoxicity blocking studies suggested that NKTa and NKTb may represent functionally distinct epitopes of this 90-kDa molecule. Anti-NKTa uniformly blocked the cytotoxicity of both JT9 and JT10 cells when tested against 11 randomly selected target cell lines. In contrast, anti-NKTb totally blocked the cytotoxicity of these cloned cells against some targets (i.e., HPB-ALL, Nalm-1) but had very little effect when cytotoxicity was measured against other target cells (i.e., K562, U937, KG-1). This selective blocking effect, therefore, supports the notion that the heterodimer defined by the NKT antibodies is involved in the process of target cell recognition rather than in the cytolytic pathway of the cloned effector cells. Moreover, the unique functional effects of anti-NKTb suggest that additional levels of complexity exist in the specific recognition mechanisms of these clonal populations of NK active mature T lymphocytes.